Rational design of triple-bridged dinuclear ZnIILnIII-based complexes: a structural, magnetic and luminescence study. Issue 2 (14th December 2016) - Zabala-Lekuona, A.; Cepeda, J.; Oyarzabal, I.; Rodríguez-Diéguez, A.; García, J. A.; Seco, J. M.; Colacio, E.
Abstract : Twelve dinuclear Zn II –Ln III complexes have been prepared and magnetically (SIM behaviour) and photophysically (luminescence) characterized. Abstract : Twelve novel dinuclear Zn II –Ln III complexes of general formula [Zn(μ-L)(μ-OAc)Ln(NO3 )2 ] (Ln III = Y (1 ), Pr (2 ), Nd (3 ), Sm (4 ), Eu (5 ), Gd (6 ), Tb (7 ), Dy (8 ), Ho (9 ), Er (10 ), Tm (11 ), Yb (12 )) have been prepared from the symmetric compartmental Mannich base ligand N, N ′-dimethyl- N, N ′-bis(2-hydroxy-3-methoxy-5-methylbenzyl)-ethylenediamine (H2 L). Structural determinations indicate that in all these complexes, Zn II ions are pentacoordinated in the inner position of the ligand, linked to two nitrogen and two oxygen atoms from L 2− and a bridging syn – syn acetate group. The Ln III ions are nonacoordinated in the outer position, linked to four oxygen atoms from L 2−, two bidentate nitrate anions and the bridging acetate. Complexes3, 6, 7, 8, 10 and12 exhibit field induced slow relaxation of the magnetization. It should be remarked that this behaviour is very infrequent in Gd III and Nd III coordination compounds. For compounds8 and12, it was possible to extract the effective energy barrier ( U eff ) for the reversal of the magnetization, with a value of 27.5 K (52.6 K considering the Raman relaxation process in addition to the Orbach mode) and 13.2 K for Dy III and Yb III compounds, respectively. Moreover, the photophysical properties of these complexes have been studied at different temperatures and show that L 2− is able to sensitize luminescence emission of many lanthanide ions. Sm III, Eu III, Tb III, Dy III and Tm III -based compounds show fluorescence in the visible region, whereas the Yb III -based one is sensitized in the near-infrared (NIR) region. Therefore, complexes7, 8 and12 may be considered as dual magneto-luminescent materials.